Penerapan Delik Permufakatan Jahat dalam Putusan Perkara Tindak Pidana Korupsi - Monica Virga Darmawan; R. Rahaditya (Dinasti Research, 2025)
Corruption is an extraordinary crime that continues to pose a significant challenge for Indonesia, with highly detrimental impacts on both the country’s finances and public trust in the government. One of the legal efforts used to combat corruption is the application of the crime of conspiracy in corruption offenses. This crime regulates the existence of agreements or collusion among several parties involved in a corrupt act, prior to the actual commission of the crime. The primary goal of applying the conspiracy crime is to prevent corrupt actions from the planning stage, which often involves multiple parties and is carried out in a structed manner. This research aims to analyze the application of conspiracy crimes in corruption offenses in Indonesia, as well as to assess the effecrtiveness and challenges faced in its implementation. The research method used in this study is normative legal research, which examines the normative aspects of legal regulations. This study employs data collection techniques in the form of library research sourced from legislation, books, scientific journals, papers, and articles related to conspiracy in corruption offenses. The application of conspiracy crimes faces significant challenges, particularly regarding the proof of shared intent or agreement among perpetrators, which is often difficult to detect because such actions are usually planned implicitly. On the other hand, conspiracy crimes are crucial for uncovering organized corruption networks, where several individuals collaborate to manipulate policies or budgets for personal or group interests. Therefore, the application of this crime becomes key in efforts to achieve more effective and effecicient corruption prevention.